EVALUATING THE ENTREPRENEURSHIP CURRICULUM: A STRUCTURAL EQUATION MODELLING ANALYSIS - Abu Bakar Yusuf; Mohd Arifin Ghazali; Nor Hasnida Md Ghazali; Mohd Afifi Bahurudin Setambah; NorAzlin Muhd Rusdin, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
There is a vital need in producing knowledgeable and skillful human capital in facing the world today. All curriculum in community colleges must be implemented in an organized way as to improve the students’ readiness to become an entrepreneur later in life. The study aims to evaluate the implementation of the entrepreneurship curriculum in community colleges, the institutions from technical and vocational education and training. The evaluation is based on the CIPP Model (context-input-process-product) regarding all the four dimensions – context, input, process and product. A random sampling technique was applied to collect data from 450 students in community colleges. The questionnaire is developed by the researchers based on the Daniel Stufflebeam CIPP evaluation format. A structural equation modelling software called Analysis of Moment Structures (AMOS) was applied to test the hypotheses. The findings showed that overall respondents agree that the implementation was at high level. The results revealed a reasonable fit with the curriculum evaluation model with an interrelationship between all the four dimensions of evaluations. Theoretical, methodological and practical implications are discussed. In short, this study provides support for the effectiveness of the curriculum implementation in community colleges.